Evolutionary dynamics and temporal/geographical correlates of recombination in the human enterovirus echovirus types 9, 11, and 30. - Leitch, E. C. McWilliam; Cabrerizo, M.; Cardosa, Mary Jane; Harvala, H.; Ivanova, O.E.; Kroes, A.C.M.; Lukashev, A.; Muir, P.; Odoom, J.; Roivanen, M.; Susi, P.; Trallero, G.; et al. (American Society for Microbiology, 2010)
The relationship between virus evolution and recombination in species B human enteroviruses was investigated through large-scale genetic analysis of echovirus type 9 (E9) and E11 isolates (n 85 and 116) from 16 European, African, and Asian countries between 1995 and 2008. Cluster 1 E9 isolates and genotype D5 and A E11 isolates showed evidence of frequent recombination between the VP1 and 3Dpol regions, the latter falling into 23 (E9) and 43 (E11) clades interspersed phylogenetically with 46 3Dpol clades of E30 and with those of other species B serotypes. Remarkably, only 2 of the 112 3Dpol clades were shared by more than one serotype (E11 and E30), demonstrating an extremely large and genetically heterogeneous recombination pool of species B nonstructural-region variants. The likelihood of recombination increased with geographical separation and time, and both were correlated with VP1 divergence, whose substitution rates allowed recombination half-lives of 1.3, 9.8, and 3.1 years, respectively, for E9, E11, and E30 to be calculated. These marked differences in recombination dynamics matched epidemiological patterns of periodic epidemic cycles of 2 to 3 (E9) and 5 to 6 (E30) years and the longer-term endemic pattern of E11 infections. Phylotemporal analysis using a Bayesian Markov chain Monte Carlo method, which placed recombination events within the evolutionary reconstruction of VP1, showed a close relationship with VP1 lineage expansion, with defined recombination events that correlated with their epidemiological periodicity. Whether recombination events contribute directly to changes in transmissibility that drive epidemic behavior or occur stochastically during periodic population bottlenecks is an unresolved issue vital to future understanding of enterovirus molecular epidemiology and pathogenesis.